Pembentukan Varietas Kedelai Tahan Cekaman Air Dari Genotipe Hasil Mutasi Gen Generasi Mutan Kedua (M2) Dengan Potensi Hasil Yang Tinggi - Aminah, Aminah; Djufry, Fadjry; Edy, Edy; Abdullah, Abdullah; Nuraeni, Nuraeni; Numba, Sudirman; Palad, Marliana S.; Syam, Amiruddin; Sahur, Asmiaty (Jurnal Penelitian Pertanian Terapan, 2023)
The aim of the study was to obtain second generation mutant lines (M2) from three gene-mutated soybean seeds, namely M2 Anjasmoro, M2 Argomulyo and M2 Dena-1 which are tolerant to drought stress, water saturation stress and high yield potential. The research was carried out in the Maros district, South Sulawesi, July-November 2022, arranged in a split plot design. The main plot is the application of water consisting of three levels, namely selection of drought stress (C1), selection of water saturation stress (C2) and selection of optimum conditions (C3). Subplots are three second generation soybean seeds resulting from gene mutations (M2), namely: M2 Anjasmoro, M2 Argomulyo and M2 Dena-1. The results showed that the best plant agronomic characters for growth and production factors were M2 Anjasmoro for water saturation stress treatment and M2 Argomulyo and M2 Dena-1 for drought stress treatment. The fastest harvesting age was obtained from the combination of drought stress and M2 Argomulyo, namely 79 days and not significantly different from the combination of drought stress and M2 Dena-1, namely 79.34 days, but significantly different from the other treatment combinations. The production obtained from the seeds resulting from the second generation of gene mutations has begun to show a difference between those given the mutation treatment and their parents, where the combination of water saturation stress and M2 Anjasmoro gave the highest production of 3.20 tonnes/ha higher than the production of its parents which only reached 2. .03-2.25 tonnes/ha. Generation M2 Argomulyo seeds were the longest surviving seeds to recovery from drought stress (38 days), in the sense that M2 Argomulyo seeds were more resistant to drought stress than the other two generations of seeds, namely M2 Anjasmoro (36 days) and M2 Dena-1 (37 days). Meanwhile, the resistance to water saturation was shown by M2 Dena-1 generation seeds, namely 40.67 days, followed by M2 Argomulyo 29.67 days and M2 Anjasmoro 27.33 days.